PERANAN HUKUM DALAM EKONOMI PASAR - fachrodin (Institut Agama Islam Hasanuddin Pare, 2023)
ABSTRACT Core from market economics is the happening of decision decentralization go together “what”, “how many”, and “way of” production process. Every individual given by a freedom to take the decision. This matter also mean that in mechanism of market economics of there are quite a lot independent individual is good the than producer side and also from consumer side. Market economics for some of circle trusted can bring the economics up at more of efesien, whereabout existing resource in economics can be exploited in more optimal, as well as is not needed by the existence of planning and observation from party manapun. internal issue formula this study: 1) How market economics of Indonesia walk matching with expected 2) How market economics with the existing economic law institute?. Pursuant to solution result, hence earn inferential that: 1) So that earning market economics of Indonesia walk matching with expected, that is can make the Indonesia economics become more efesien, very determined by support from strong economic law institute. Without existence of support from difficult strong economic law institute for market economics earn the bejalan well 2) Market economics with the institute of economic law represent one inherent union, though sometimes growth of institute of economic law is always left behind from market economics growth. But institute of economic law ought to earn always keep abreast of the market economics. Keywords: Role Punish, Market Economics